Mobile Learning Berbasis Android sebagai Media Pembelajaran PAI di Era Revolusi Industri 4.0 - Jaenullah, Jaenullah (Jurnal Teknologi Pembelajaran, 2025)
The development of communication technology in the era of the Industrial Revolution 4.0 has an impact on various aspects of life, including education. This demands that educators create an active, innovative, creative, effective, and enjoyable teaching and learning process. However, in Islamic Religious Education (PAI) lessons, it is often still monotonous and less engaging, which makes students feel bored. On the other hand, the rapid development of communication technology, especially the use of Android devices, presents a great opportunity to create innovations in learning. To address this, PAI teachers at SMK Ma’arif Metro Lampung have innovated by utilizing Android-based mobile learning as a learning medium. This step was taken because the majority of students are already accustomed to using Android devices in their daily lives. This study aims to assess the extent of the utilization of Android-based mobile learning as a learning medium for PAI at SMK Ma’arif Metro Lampung. The research uses a qualitative method, with data collection conducted through observations and direct interviews. Data sources include school archives, the school's website, as well as interviews with the school principal, PAI teachers, and students. The results show that the implementation of Android-based mobile learning as a medium for PAI lessons at SMK Ma’arif Metro Lampung is going well. Although there are some obstacles, such as signal issues and classroom management, the use of mobile learning has proven to be effective and has increased students' interest in PAI learning.